Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a)\frac{7}{3}-\frac{4}{3}\times x=\frac{5}{6}\)
\(-\frac{4}{3}\times x=\frac{3}{2}\)
\(x=\frac{-9}{8}\)
\(b)\frac{7}{4}-\frac{3}{4}\times x=\frac{5}{6}\)
\(-\frac{3}{4}\times x=\frac{11}{12}\)
\(x=-\frac{11}{9}\)
1) (X-6)x(2x - 6)=0
=> X - 6 = 0 => x = 0 + 6 = 6
=> 2x - 6 = 0 => 2x = 6 => X = 6 : 2 = 3
Vẫy x{6; 3}
2) 100:(x-7)=1
x-7 = 100:1
x-7 = 100
x = 100 + 7
x = 107
a/ => 7(x + 1) = 119
=> x + 1 = 17
=> x = 16
b/ => 3x - 6 = 33 = 27
=> 3x = 33
=> x = 11
\(36\div\left[7.\left(x-3\right)+4\right]=6\)
\(\Rightarrow7.\left(x-3\right)+4=36\div6\)
\(\Rightarrow7.\left(x-3\right)+4=6\)
\(\Rightarrow7.\left(x-3\right)=6-4\)
\(\Rightarrow7.\left(x-3\right)=2\)
\(\Rightarrow x-3=2\div7\)
\(\Rightarrow x-3=\frac{2}{7}\)
\(\Rightarrow x=\frac{2}{7}+3\)
\(\Rightarrow x=\frac{23}{7}\)
\(36:\left[7.\left(x-3\right)+4\right]=6\)
\(7.\left(x-3\right)+4=36:6\)
\(7.\left(x-3\right)+4=6\)
\(7.\left(x-3\right)=6-4\)
\(7.\left(x-3\right)=2\)
\(x-3=2:7\)
\(x-3=\frac{2}{7}\)
\(x=\frac{2}{7}+3\)
\(x=\frac{23}{7}\)
1/ -8+13-...+x=250
2/ 1-3+5-7+...-x=-600
3/ -2+4-6+8-...+x=100
4/ 2-6=10-14+...-x=-800
giúp mình với nha
chiu hhhhhhhhttttttttttttttttnnnnnnnnnnnnnnnnnng
3x-21=6
<=>3x=27
=>x=9